Health economic evaluation of structured education programs for patients with diabetes: a systematic review - Caihua Ye; Qiwei Zhou; Wenfei Yang; Libo Tao; Xinjun Jiang (Frontiers in Public Health)
BackgroundDiabetes structured education programs have been demonstrated to effectively improve glycemic control and self-management behaviors. However, evidence on the health economic evaluation of these programs is limited.ObjectivesTo systematically review the health economic evaluation of structured education programs for patients with type 1 and type 2 diabetes mellitus.MethodsThe English databases PUBMED, WEB OF SCIENCE, OVID, COCHRANE LIBRARY, EMBASE, and EBSCO, along with the Chinese databases CNKI, WANFANG, VIP, and SINOMED, were searched from their inception to September 2024. The quality of the literature was assessed using the CHEERS 2022 checklist. A descriptive analysis was performed on the studies included in the review, with all currencies converted to international dollars. An incremental cost-effectiveness ratio of less than one times the per capita GDP was considered highly cost-effective, while a ratio between one and three times the per capita GDP was considered cost-effective.ResultsA total of 28 studies from upper-middle-income and high-income countries were included. The average quality score of the included studies was 18.6, indicating a moderate level of reporting quality. Among these, eleven studies demonstrated that diabetes structured education programs were highly cost-effective and twelve were found to be cost-effective. In contrast, three studies were deemed not cost-effective, and two studies provided uncertain results. The ranges of the incremental cost-effectiveness ratios for short-term, medium-term, and long-term studies were − 520.60 to 65,167.00 dollars, −24,952.22 to 14,465.00 dollars, and −874.00 to 236,991.67 dollars, respectively.ConclusionThis study confirms the cost-effectiveness of structured education programs for diabetes and highlights their importance for patients with type 2 diabetes who have HbA1c levels exceeding 7% and are receiving non-insulin therapy. Additionally, the potential advantages of incorporating telecommunication technologies into structured diabetes education were emphasized. These findings offer valuable insights and guidance for decision-making in diabetes management and clinical practice, contributing to the optimization of medical resource allocation and the improvement of health status and quality of life for patients.